Trends of hip arthroscopy in Italy show an increase over the years: A nationwide study from 2001 to 2016 - Umile Giuseppe Longo; Rocco Papalia; Sergio De Salvatore; Giovanni Intermesoli; Ilaria Piergentili; Stefano Zaffagnini; Kristian Samuelsson; Pieter D'Hooghe; Vincenzo Denaro (Journal of Experimental Orthopaedics, 2024)
Abstract Purpose Hip arthroscopy has gained popularity among orthopaedic procedures over the last decade. The present study aims to evaluate the trends of hip arthroscopy procedures in Italy analysing data recorded by the Italian Ministry of Health, reporting demographics, length of hospitalisation (LOS), diagnosis and the economic impact of the procedure. Methods The National Hospital Discharge records reported by the Italian Ministry of Health were used, analysing the data regarding hip arthroscopy procedures performed in Italy between 2001 and 2016. A total of 4022 hip arthroscopies were performed in Italy in the adult population. Results The present study shows more males being exposed to the procedure, while the mean age of females was always higher than that of males during the 16‐year study period. The mean LOS was 2.6 ± 3.2 days, and every procedure had a mean Italian hospital reimbursement from 1361€ to 1512€. Hip arthroscopy procedures have increased substantially between the years 2001 and 2016, as well as the costs related to the surgery. Conclusions The findings of this study constitute valuable clinical and scientific evidence for the healthcare system, which is useful not only for the formulation and improvement of national healthcare policies but also to improve awareness and accessibility of hip arthroscopy. Level of Evidence Level II.